2005
DOI: 10.1086/502612
|View full text |Cite
|
Sign up to set email alerts
|

A Large Outbreak of Hepatitis B Virus Infections Associated With Frequent Injections at a Physician's Office

Abstract: Administration of unnecessary injections combined with failure to separate clean from contaminated areas and follow safe injection practices likely resulted in patient-to-patient HBV transmission in a private physician's office.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…1 During the last decade, several HBV outbreaks caused by nosocomial and iatrogenic transmission have been reported in developed countries. [2][3][4][5][6] These findings indicated that these routes of trans- mission, e.g. multi-dose vials, dental equipments, dialysis units, transplant organs, finger stick sampling and surgical procedures, still exist despite all efforts to make health care workers and medical staff aware of HBV transmission risks.…”
mentioning
confidence: 99%
“…1 During the last decade, several HBV outbreaks caused by nosocomial and iatrogenic transmission have been reported in developed countries. [2][3][4][5][6] These findings indicated that these routes of trans- mission, e.g. multi-dose vials, dental equipments, dialysis units, transplant organs, finger stick sampling and surgical procedures, still exist despite all efforts to make health care workers and medical staff aware of HBV transmission risks.…”
mentioning
confidence: 99%
“…7 The epidemic was identified when two low-risk patients were detected as having acute HBV infection. These two patients had no identifiable risk factors for HBV infection, but did attend the same physician's practice.…”
Section: Table* Strategies T O P R E V E N T Occupational Exposures Amentioning
confidence: 99%
“…7 The medications most frequently administered in this practice were vitamin B12, atropine, and dexamethasone in injections that combined two of these agents or all three in one syringe. 7 These medicines accounted for 90% of the injections in this practice.…”
Section: Table* Strategies T O P R E V E N T Occupational Exposures Amentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, several HBV outbreaks caused by nosocomial and iatrogenic transmissions have been reported in developed countries (9)(10)(11)(12)(13)(14)(15)(16). These findings indicate that several routes of transmission (i.e.…”
mentioning
confidence: 95%